Distanced Data: Transcribing Other People’s Research Tapes - Tilley, Susan; Powick, Kelly (Canadian Journal of Education/Revue canadienne de l'éducation, 2002)
In this article, we report on our qualitative study involving eight individuals hired to transcribe research tapes in university contexts. We consider issues of data analysis and data trustworthiness and the implications for both when transcription is assigned to someone other than the researcher. We explore the challenges transcribers faced completing their work, transcription decisions they made in situ, and the effects of the transcribers’ degree of investment in the research on the transcripts produced. We highlight the need for researchers to acknowledge transcription as an important aspect of the research process and take seriously the decision of who transcribes. Keywords: transcription, qualitative methodology, data trustworthiness, interviewing, research assistants Cet article offre un compte-rendu d’une étude qualitative concernant huit individus embauchés pour transcrire des cassettes de recherche dans un contexte universitaire. Nous étudions la problématique de l’analyse des données, de la fiabilité des données et du rôle qu’elles jouent dans la transcription accomplie par quelqu’un d’autre que le chercheur. Nous explorons les défis auxquels les préposés à la machine à transcrire font face dans la réalisation de leur travail, dans leurs décisions in situ et les effets sur la transcription finale de leur niveau d’investissement dans la recherche. Nous soulignons le besoin que les chercheurs reconnaissent la transcription comme un aspect important du processus de recherche et de prendre au sérieux le choix de ceux qui font la transcription. Mots-clés: transcription, méthodologie qualitative, fiabilité des données, entrevues, assistants de recherche